Worsening Workers' Health by Lowering Retirement Age: The Malign Consequences of a Benign Reform - Ann Barbara Bauer; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2018)
In 2003, the retirement age of Swiss construction workers was lowered from 65 to 60. This reform has been intended to improve their health. Our study shows the opposite outcome. The human capital theory suggests that investments in employees' productivity by the employer and the employees themselves depend on the time remaining until their retirement. Hence, we hypothesize that pension reforms that reduce employees' working horizon decrease investments in work-related human capital, which translates into a higher prevalence of sickness absences, a longer absence duration, and worse health. By econometrically comparing pre- and post-reform cohorts of construction workers with other blue-collar workers, we find that among 56–60-year-old construction workers, their sickness absences increase from 3.2% to 5.6%, their sickness duration increases by 33%, and their probability of having health problems increases from 9% to 12.7% due to the reform.
Keywords: I12; J14; J26; L74; 330; Pension reform; natural experiment; construction worker; sickness absence; sickness duration; poor health